Gregorio de Tours y la hagiografía del siglo VI Aproximaciones histórico-teológicas al libro "Sobre las virtudes de san Martín" = Gregory of Tours and hagiography in the sixth century : historical and theological approaches to the book "About the virtues of Saint Martin" - Aguirre Durán, Marcelo 1977- (2020)
El obispo Gregorio de Tours († 594) redactó ocho libros hagiográficos, cuatro de los cuales fueron dedicados a los milagros realizados por san Martín –De uirtutibus sancti Martini episcopi–. Esta recopilación de favores, poco difundida en el mundo hispanohablante, representa un esfuerzo pedagógico-moral y permite comprender el proyecto pastoral de este escritor galorromano del siglo VI. El presente trabajo intenta mostrar cómo la labor hagiográfica de este letrado obispo posibilita el análisis de las particularidades históricas de una sociedad eminentemente religiosa, en la cual la transmisión de los ideales de una disciplina de vida evangélica y la propagación de la devoción a san Martín resultan centrales.
Bishop Gregory of Tours († 594) wrote eight hagiographical books, four of which were dedicated to the miracles performed by Saint Martin –De uirtutibus sancti Martini episcopi–. This collection of favours, little known in the Spanish-speaking world, represents a pedagogical and moral effort and allows us to understand the pastoral project of this sixth century Gallo-Roman writer. The present work aims to show how the hagiographical work of this learned bishop makes possible the analysis of the historical particularities of an eminently religious society, in which the transmission of the ideals of a discipline of evangelical life and the spread of devotion to Saint Martin are central.
Keywords: Gregorio de Tours; Martín de Tours; Hagiografía; Milagros